Effects of different LED light colors on growth performance and harmful gas emission of broilers breeding in a digital rearing chamber - Jie, Dengfei; Zhang, Zhanxiang; He, Jincheng; Zhou, Yafang; Zhu, Guangyou (International Journal of Agricultural and Biological Engineering, 2022)
Refined management is an inevitable trend in the development of livestock husbandry. Accurate acquisition of breeding environment parameters is beneficial to improve breeding efficiency while reducing the environmental pollution. Light is an important breeding environmental factor during broiler breeding. In this study, a short-term broiler breeding experiment was conducted with different light color illumination environments in a digital breeding chamber under lab conditions. According to experimental results, the Red Light (RL) group was conducive to the growth of broilers at 30 d of age with low NH3 emission concentration; the Green Light (GL) group inhibited the broiler growth; the Yellow Light (YL) group showed the highest average emission concentration of NH3 and lowest daily average emission concentration of CO2. According to the analysis of moisture content, pH value, and C/N in the broiler manure, it can be concluded that the physical and chemical properties of broiler defecation quantities were different under various light color illuminations, resulting in the difference in broiler growth conditions and harmful gas emissions. The study results could provide a research basis and ideas of reference to establish a relationship between LED illumination information, broiler growth performance, and harmful gas emission. Keywords: broiler, growth properties, harmful gas, ammonia, illumination environment DOI: 10.25165/j.ijabe.20221504.6766 Citation: Jie D F, Zhang Z X, He J C, Zhou Y F, Zhu G Y. Effects of different LED light colors on growth performance and harmful gas emission of broilers breeding in a digital rearing chamber. Int J Agric & Biol Eng, 2022; 15(4): 71–78.